An L-shaped and bending-torsion coupled beam for self-adaptive vibration energy harvesting - Huang, Yi (2023)
Vibration energy harvesting is promising for powering wireless sensor networks for mechanical equipment monitoring. Considering the broadband feature of ambient vibrations, a novel L-shaped self-adaptive piezoelectric energy harvester (LSA-PEH) with a slider is proposed. A linearized mathematical model of the LSA-PEH is established to obtain the relationship between its resonant frequency and the slider position. The maximum resonant frequency that can be achieved by the LSA-PEH is predicted based on the linearized model. The corresponding condition is to fix the slider at around 0.08 m, which is a nodal point. Moreover, the theoretical model explains why the slider moves back and forth when the excitation frequency is 40 Hz. Experimental results show that the slider of the proposed LSA-PEH can passively relocate its position to adjust its resonant frequency and maintain resonance. By the same criteria, the bandwidth of the proposed LSA-PEH is increased by 350% compared to a conventional L-shaped beam harvester.